Moisture content and support value in cohesive soils in the Independence district (Aporte Santiaguino, 2024)
In this research, the objective was to determine the incidence and relationship of moisture content (CH) in the Support Value (CBR) and density for 12, 26 and 55 strokes per layer for the cohesive soil at the subgrade level of the Shancayan neighborhood. -Huaraz-Ancash, with which CBR isoline maps were created using Excel and OriginPro 2019b. The method is deductive, quantitative approach, experimental and transversal design. The instruments used are data collection sheets, laboratory formats. The sources used are the MTC, scientific article, thesis, books. The results for 0.1” and 0.2” penetration show CBR and Density values ​​that increase and then decrease for different CH. Finally, it is concluded that for values ​​of 13.5%, 12.5% ​​and 10.45% for 12, 26 and 55 strokes per layer respectively, the relationship of the CH with the CBR value above the optimal moisture content (CHO), have an inverse relationship. proportional. The opposite happens for the relationship between CH and the density value below CHO.
Keywords: Cbr; Moisture Content; Compaction Energy